Konsep Penentuan Upah dalam Ekonomi Islam - Sri Dewi Yusuf (Al-Ulum, 2010)
This article explains the concept of wages in Islamic perspective. In fact, most workers are not rewarded as equally as their achievement. This can trigger a conflict between workers and employers. By contrast, most entrepreneurs faced with unstable economic conditions. In that position, the workers often become victims of the employers to accept wages that are not feasible. This condition causes the peak the workers go to street for demonstration or strike. The role of government; therefore, is needed in setting minimum wage standards. Injustice can cause confusion for workers and strike. Its impact can affect economic sectors. For these reasons, Islam offers a solution to the problem of wages and the interests of both parties without violating the rights of both.